South Africa : Financial Sector Assessment Program-Technical Note on Systemic Liquidity Management. (IMF Staff Country Reports; Country Report, 2022)
The South African financial markets are the most developed and liquid in Africa and well developed by global standards, as well, reflecting credible and independent policy making, a diverse economy and strong financial institutions. Foreign exchange market turnover is consistently among the top 20 in the world according to the Bank for International Settlement (BIS) triennial survey. The government bond and interest rate swap yield curves go out to 20 years. The size of the domestic bond market is around 85 percent of GDP, and stock market capitalization is about 300 percent of the GDP. Supporting financial market infrastructure is broadly adequate for the size and turnover of the markets. The central bank (SARB) operates independently and at a high capacity, providing a sound footing for market functioning.